Instrument of self-perception and knowledge of dental erosion: cross-cultural adaptation to the Brazilian population - Sandro Bertazzo SILVA; Tanise de Medeiros CABRAL; Tatiana Militz Perrone PINTO; Letícia Brandão DURAND (Sociedade Brasileira de Pesquisa Odontológica, 2015)
There are few instruments available in Brazil for obtaining data on dental erosion among adults. For this reason, the interview entitled "A Survey on Hong Kong People's Dietary Behavior in Relations to Acid Erosion", published in English, was considered for translation. The aim of this study was to perform a cross-cultural adaptation and content validation for the Brazilian population. After obtaining the author's permission, the interview underwent several stages: translation, back translation, review by a bilingual person and a committee of experts, administration of the English instrument and of the Portuguese version to a bilingual group, and pretesting in a convenience sample of 50 adults. The interview was translated and adapted to the Portuguese language and the Brazilian culture. The analysis of the data revealed that the interview was easy to apply, conduct and understand; therefore, it was considered viable and capable of being used in different studies.